PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE HOLLYWOOD SQUARES REVIEW TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMP NEGERI 23 PADANG - Putra, Rio Eka; Husna, Husna; Fitri, Dewi Yuliana (STKIP PGRI Sumbar, 2013)
The research was based on low of students math concept comprehension at SMPN 23 Padang. The research is to aims determine students math concept comprehension with Hollywod Squares Review strategy better than students math concept comprehension with conventional learning. The research is experimental by using Random Sampling. Population is students in the class VII SMPN 23 Padang. The instrument used is examination with reliability 0,873. To test hypothesis used t-test one side with MINITAB, obtained P-Value 0,008 less than Î± = 0,05, so hypothesis received. In conclusion, students math concept comprehension with Hollywood Squares Review strategy better than students math concept comprehension with conventional learning. Â